A new genus and species of Typhinae (Mollusca, Gastropoda, Muricidae) from off northeastern Brazil - Absalão, Ricardo Silva; Santos, Franklin Noel Dos (Zootaxa, 2003)
A new member of the marine gastropod muricid subfamily Typhinae was discovered during dredgings off the continental shelf of northeastern Brazil. Although its four varices per whorl and the presence of sealed anal tubes (except for then anterior most one) suggest its placement in this subfamily, the taxon accords with no known genera. Brasityphis barrosi n. gen. and n. sp. is characterised by its small size, the absence of any partition, and the presence of five strong rounded denticles within the outer lip and a callus on the anterior of the parietal wall.